Event-centric summary generation - Vanderwende, Lucy; Banko, Michele; Menezes, Arul (Working notes of the Document Understanding Conference 2004, 2004)
The Natural Language Processing Group at Microsoft Research participated in Task 2 of the Document Understanding Conference for the first time in 2004. Our primary interest is two-fold: 1) to explore an event-centric approach to summarization, 2) to explore a generation approach to summary realization.